Immunohistological characterization of the decidual leucocytic infiltrate related to endometrial gland epithelium in early human pregnancy. - Bulmer, J N (1985)
The leucocytic infiltrate which is associated with maternal endometrial glands in decidual tissue in early human pregnancy has been shown by immunohistology to consist mainly of macrophages and T lymphocytes. Cells expressing HLA-DR were prominent around the glands, and most were also reactive for the Leu-M3 tissue macrophage antigen. In addition, HLA-DR-positive T cells were identified by double immunoenzymatic labelling, situated both immediately adjacent to the gland epithelium and in adjacent aggregates. Some accumulation of HLA-DR-positive cells has also been noted around the glands in non-pregnant endometrium during the mid and late secretory phases, and occasional T6 antigen-bearing cells were also detected. Occasional HLA-DR-positive surface and gland epithelial cells were observed in both pregnant and non-pregnant specimens. These results indicate that, in early human pregnancy, the endometrial glands may be subject to a form of active immune response partially under hormonal control.